Στρατός και κοινωνία στο ύστερο Βυζάντιο: το μεταρρυθμιστικό πρόγραμμα του Γεωργίου Γεμιστού Πλήθωνα - ΣΥΓΚΕΛΛΟΥ Eυστρατία (Byzantina Symmeikta, 2015)
Army and Society in Late Byzantium: the reform program of George Plethon Gemistos In the early 15th century the Byzantine state was surrounded by the Ottomans, whereas the Peloponnese was the last defensive stronghold of the Byzantines in the Greek area. There, the need of defense became a major social issue and provided matter for discussion about the institutional and social function of the army. Plethon’ s proposals for the establishment of local professional army, as formulated in his texts addressed to the emperor Manuel II Palaeologus and the despot Theodore are associated with the social and economic reformation of the region and reflect the general need for the political reorganization of the Byzantine Empire. This paper examines Gemistos’ reform program regarding the military and political-economic conditions of the era. The thoughts of the philosopher of Mystras on the Byzantine army, which have occupied scientific research from time to time, re-evaluated in order to emphasize the role of the army in the society of the late Byzantine period. The latter remains as powerful as necessary in the contest of a revived Byzantine state.